Bortezomib Induced Tumor Lysis Syndrome in Multiple Myeloma - Yu, Shinae; Ryu, Sung Woo; Kim, Kyoung-Ha; Kim, Se-Hyoung; Lee, Nam-Su; Park, Sung-Kyu; Won, Jong-Ho (Soonchunhyang medical science, 2013)
The tumor lysis syndrome (TLS) commonly occurs in the lymphoproliferative disorder, either spontaneously or in response to therapy. TLS is uncommon in multiple myeloma. However, with the use of bortezomib in the treatment of multiple myeloma, cases of TLS have been reported. We report here threepatients who presented with TLS after the administration of bortezomib. Two of them presented mild symptoms and recovered with hydration only. However, death of the other patient was associated with TLS. We should monitor patients who had high tumor burden, especially in early phase of bortezomib therapy and appropriate prophylaxis for high risk patient is also needed. KCI Citation Count: 0